Approaching e-commerce from an economic perspective (Revista de Investigaciones Universidad del Quindío, 2022)
Trade is an economic activity of buying and selling products or services to meet the needs of society. It has existed for several years evolving in various ways as it was with the implementation of technology with it adapted to be able to continue progressing and was born what is known as electronic commerce which is carried out through the internet by specialized sites where the purchase and sale of products is available to everyone facilitating their acquisition processes, the use of technology to trade has caused the economy to have an exponential growth, this is because in recent years the acquisition through the internet has been increasing. This research will describe in a documentary way how electronic commerce has had an impact for the economy to grow and develop with the help of new technological tools.
Keywords: trade; economy; society; technology